Real inclusion or simulation? An exploration of an advertising campaign for the gay community in Mexico - Martínez Martínez, Cinthya; Rodriguez Lucio, Claudia Ivette; Tovar Herrera, Jose Roberto; Montiel, Oscar (2020)
The gay community has generally been stereotyped and excluded from spaces in our society. This is reflected in political or commercial advertising campaigns, with those that have been inclusive being very scarce at a global level. With the aim of analyzing the mechanisms in the current dynamics of advertising campaigns, the present case study makes a literature review and a reflection on this social fact, addressing the feasibility and need to give voice to this community, making a critical analysis of the importance of being inclusive in today's society, suggesting a proposal based on Gross (2001) model applied in advertising campaigns for the gay community in Mexico, and Moreno (2006), that could lead to a huge potential for both Mexican companies and advertising agencies to address this community, not only as a market element, but also as an element of social justice. The results suggest that the existing gap in advertising is evident both in Mexico and Latin American context and including these communities seems to be relevant for both its economies and societies.